2011
DOI: 10.1029/2011gl047984
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt warming of the Red Sea

Abstract: Coral reef ecosystems, often referred to as “marine rainforests,” concentrate the most diverse life in the oceans. Red Sea reef dwellers are adapted in a very warm environment, fact that makes them vulnerable to further and rapid warming. The detection and understanding of abrupt temperature changes is an important task, as ecosystems have more chances to adapt in a slowly rather than in a rapid changing environment. Using satellite derived sea surface and ground based air temperatures, it is shown that the Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
105
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 21 publications
10
105
0
Order By: Relevance
“…In particular, the RSOW flows out to the Indian Ocean (Bower et al 2000(Bower et al , 2005Aiki et al 2006) and is traced as a maximum salinity intermediate water in the northwestern Indian Ocean, reaching as far as the southeastern coast of Africa (Fine et al 1988;Beal et al 2000). However, several studies based on modeled and remotely sensed datasets show that global warming and climate change trends are particularly evident in the Red Sea (Kleypas et al 2008;Cantin et al 2010;Raitsos et al 2011). This could potentially lead to fewer convection events because of positive surface buoyancy.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the RSOW flows out to the Indian Ocean (Bower et al 2000(Bower et al , 2005Aiki et al 2006) and is traced as a maximum salinity intermediate water in the northwestern Indian Ocean, reaching as far as the southeastern coast of Africa (Fine et al 1988;Beal et al 2000). However, several studies based on modeled and remotely sensed datasets show that global warming and climate change trends are particularly evident in the Red Sea (Kleypas et al 2008;Cantin et al 2010;Raitsos et al 2011). This could potentially lead to fewer convection events because of positive surface buoyancy.…”
Section: Introductionmentioning
confidence: 99%
“…, and it is considered one of the warmest seas in the world (Morcos 1970;Ahmad and Sultan 1989;Sofianos and Johns 2002;Belkin 2009;Raitsos et al 2011). The consequent water deficit is counterbalanced by an inverse estuarine flow through the narrow (25 km wide) Bab el Mandeb Strait at the southernmost edge of the basin (Murray and Johns 1997;Sofianos and Johns 2002;Yao et al 2014a,b).…”
mentioning
confidence: 99%
“…It is interesting how changing surface winds (Papadopoulos et al 2013;Abualnaja et al 2015) can affect surface evaporation, which in turn modulates local moisture transports. A sharp increase in evaporation in the 1990s that is somewhat delayed with respect to the change in SST (Raitsos et al 2011) can be also analyzed in a view of long-term changes in surface fluxes (both synchronic and lagged) modulated by the Red Sea SST and associated with longer-term intrinsic modes of the Red Sea variability. This analysis, however, requires much longer time series than those available from the modern reanalyses.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In addition to the interplay with surface turbulent fluxes, SST steers to a large extent the sea-land temperature contrasts and associated breeze-like circulation in the lower atmosphere. Raitsos et al (2011) recently reported an abrupt warming signal in the Red Sea SST in 1994-95, which has important implications for coral growth (Cantin et al 2010) but should also have a signature in the dynamics of the atmospheric moisture transports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation